Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T18:44:55+01:00
2(2x-y)+3(y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3y=42
5x+15y-16x+8y=-32

y+4x=42 /*23
23y-11x=-32 / * (-1)

23y+92x=966
-23y+11x=32

103x=998
-23y+11x=32

x=9,68
-23y=32-96,8

x=9,68
y=-2,81




2010-02-17T18:45:07+01:00
2(2x-y)+3y=42
4x - 2y + 3y = 42
4x + y = 42
5(x+3y)-8(2x-y)=-32
5x + 15y - 16x +8y = -32
-11x + 23y = -32

4x+y=42 |*11
-11x + 23y = -32 |*4

44x + 11y = 334
-44x + 92y =-128 (dodajemy)

103y = 206 |:103
y = 2

4x + 2 = 42
4x = 42-2
4x = 40 |:4
x = 10